Environmentally friendly water glass-based binder for 3D sand core printing and preparation method thereof

By using a composite water glass modified with high modulus sodium silicate and enhanced modifier, combined with modified nanoparticles and modified starch, the problem of insufficient fluidity and strength of water glass binder in 3D sand core printing is solved. , realizes efficient sand core forming and recycling, and meets green and environmental protection requirements.

CN118720045BActive Publication Date: 2025-02-25SHENYANG AIKESIBON IND MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410929523.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-02-25
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

In the prior art, water glass adhesives have poor fluidity, molding strength, moisture resistance and dispersion during the 3D sand core printing process, and are difficult to separate from castings and recycle them, which violates the concept of green and environmentally friendly manufacturing.

Method used

Using composite water glass as the binder matrix, the rich rich with enhancement enhancement is prepared by mixing the high-modulus sodium silicate and the enhanced modifier, combined with modified nanoparticles and sodium phosphate modified modified starch. Composite water glass containing sodium and potassium ions improves the fluidity and strength index of the binder.

Benefits of technology

Improve the instant strength, long-term strength and wet resistance of the sand during the 3D sand core printing process, enhance the fluidity of the mixed sand and the cracking of the adhesive, and realize the effective separation and recycling of the sand core and castings, which is in line with the Green and environmentally friendly manufacturing concept.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000009067480000031
    Figure GHA0000009067480000031
  • Figure GHA0000009067480000141
    Figure GHA0000009067480000141
  • Figure GHA0000009067480000151
    Figure GHA0000009067480000151
Patent Text Reader

Abstract

The present invention discloses an environmentally friendly water glass-based binder for 3D sand core printing and a preparation method thereof, and belongs to the field of binder processing technology. The present invention is used to solve the technical problems of poor fluidity of 3D printing mixed sand prepared by mixing water glass binder with 3D printing standard sand in the prior art and poor molding strength, moisture resistance and collapsibility of 3D printing sand cores. The environmentally friendly water glass-based binder for 3D sand core printing includes the following components by weight: 80-100 parts of composite water glass and 25-30 parts of composite accelerator. The binder prepared by the present invention can effectively improve the fluidity of 3D printing mixed sand, the 3D printed sand core can be formed immediately, the molded sample has good strength and moisture resistance, and the collapsibility of the sand core is good, no harmful gas is generated during the pouring process, and the used sand core molding sand can be recycled to reduce production costs, which is in line with the green and environmentally friendly manufacturing concept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of binder processing, and in particular to an environmentally friendly water glass-based binder for 3D sand core printing and a preparation method thereof. Background Art

[0002] With the improvement of global awareness of environmental protection and the popularization of green manufacturing concepts, the foundry industry, as an important part of the traditional manufacturing industry, has received increasing attention for its environmental protection issues; sand cores are materials used to make cores in casting production. They are generally made of a certain proportion of molding materials such as casting sand, sand binder and additives. They are mainly used to form the inner cavity of the casting, various molding holes and parts of the shape that are difficult to demold. During the casting production process, the sand core is fixed in a specific position in the sand mold and then poured. After the casting is completed, the sand core is wrapped inside the casting, and the cavity part in the casting is formed by breaking the sand core.

[0003] In recent years, 3D printing technology has been widely used in the foundry industry due to its unique advantages. The preparation of sand cores through 3D printing technology can significantly shorten the mold production cycle, achieve small batch rapid prototyping, and improve production efficiency and product quality. However, in the process of 3D sand core printing, the selection and preparation process of the binder have a crucial impact on the performance and environmental performance of the sand core.

[0004] The sand core binders in the prior art are mainly divided into two categories: organic and inorganic. Organic binders, such as resin polymers, are prone to produce toxic gases during the casting process, which are harmful to the environment and the health of operators. Inorganic binders, such as traditional water glass sand binders, have good environmental performance, but the strength of water glass sand binders is low, and the prepared 3D printing mixed sand has poor fluidity, making it difficult to apply and print the sand core in the sand core 3D printing equipment. In addition, the traditional water glass binder has poor instant strength and strong water absorption, which causes the sand core to easily creep, break and collapse during printing, seriously affecting the stability of the sand core, and the printed sand core has poor precision. In addition, when the traditional water glass binder is applied to the sand core, its addition amount often reaches 8-10%. After the molten high-temperature metal melt is poured, the sand core will be agglomerated into blocks, with poor disintegration, and it is difficult to separate it from the casting and recycle it, which does not conform to the green and environmentally friendly manufacturing concept.

[0005] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0006] The purpose of the present invention is to provide an environmentally friendly water glass-based binder for 3D sand core printing and a preparation method thereof, so as to solve the technical problems that the 3D printing mixed sand prepared by mixing the water glass binder with the 3D printing standard sand in the prior art has poor fluidity and the molding strength, moisture resistance and collapsibility of the 3D printing sand core are poor, and it is difficult to separate the sand core from the casting and recycle it, which does not conform to the green and environmentally friendly manufacturing concept.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] An environmentally friendly water glass-based binder for 3D sand core printing includes the following components in parts by weight: 80-100 parts of composite water glass and 25-30 parts of composite accelerator;

[0009] The composite accelerator is composed of an accelerator and a dispersing aid in a weight ratio of 25-35:4-6;

[0010] The accelerator is composed of modified nanoparticles and modified starch in a weight ratio of 3:1-2.

[0011] Furthermore, the composite water glass is obtained by processing the following steps:

[0012] A1, adding hydroxymethyl cellulose, polyvinyl alcohol, xylitol, sorbitol and purified water into a reaction kettle, mixing evenly, and obtaining a reinforcing modifier;

[0013] A2. Add sodium silicate solution and potassium silicate solution into the reactor and stir. Raise the temperature of the reactor to reflux the system, keep warm and stir for 30-50 minutes, lower the temperature of the reactor to 55-65°C, add the reinforcing modifier into the reactor, keep warm and stir for 40-60 minutes, and naturally cool to room temperature to obtain composite water glass.

[0014] The synthesis principle of composite water glass is:

[0015] After promoting the dissolution of silicate by high temperature, it is mixed with a reinforcing modifier to enhance the interaction between the silicate and the reinforcing modifier, so that the reinforcing modifier can strengthen the silicate and prepare a composite water glass with better performance.

[0016] Furthermore, in step A1, the weight ratio of the hydroxymethyl cellulose, polyvinyl alcohol, xylitol, sorbitol and purified water is 10-11:7-9:4-5:2-3:20-30; in step A2, the modulus of the sodium silicate solution is 2.4-3.1, the solid content is 40-45%, the modulus of the potassium silicate solution is 3.5-4.0, the solid content is 35-45%, and the weight ratio of the sodium silicate solution, potassium silicate solution and reinforcing modifier is 75-85:25-30:10-15.

[0017] Furthermore, the modified nanoparticles are obtained by processing the following steps:

[0018] B1, mixing nano silicon nitride, silicon powder and hollow glass microspheres uniformly to obtain an inorganic mixture;

[0019] B2. Add the inorganic mixture, ethyl 2-(triethoxysilyl)acetate and anhydrous ethanol into a reactor and stir. Increase the temperature of the reactor to 50-60°C, add concentrated sulfuric acid into the reactor, keep the temperature for 2-3 hours, increase the temperature of the reactor to reflux the system, keep the temperature for 8-12 hours, and perform post-treatment to obtain modified nanoparticles.

[0020] The synthetic reaction formula of modified nanoparticles is:

[0021]

[0022] Wherein, · is nano silicon nitride, silicon powder or hollow glass microspheres.

[0023] The synthetic reaction principle of modified nanoparticles is:

[0024] Under concentrated sulfuric acid conditions, the ethoxy groups on the ethyl 2-(triethoxysilyl)acetate molecules are hydrolyzed to form silanol groups, which react with the hydroxyl groups on the surface of the inorganic nanoparticles to form Si-O-Si bonds, thereby modifying the inorganic nanoparticles. In a subsequent high-temperature environment, the ethyl acetate bonds on the ethyl 2-(triethoxysilyl)acetate molecules are hydrolyzed to form hydroxyl modifications on the outside of the particles to obtain modified nanoparticles.

[0025] Furthermore, in step B1, the weight ratio of the nano silicon nitride, silicon powder and hollow glass microspheres is 2-3:1-2:3-5; in step B2, the amount ratio of the inorganic mixture, ethyl 2-(triethoxysilyl)acetate, anhydrous ethanol and concentrated sulfuric acid is 5g:2-3g:50mL:15mL, and the mass fraction of the concentrated sulfuric acid is 75-85%. The post-treatment operation includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 65-75°C and dried to constant weight to obtain modified nanoparticles.

[0026] Furthermore, the preparation method of the modified starch is: adding starch, ethanol solution and sodium hydroxide aqueous solution into a reactor and stirring, raising the temperature of the reactor to reflux the system, adding sodium tripolyphosphate aqueous solution into the reactor, reacting for 4-6 hours, and post-treating to obtain the modified starch.

[0027] The synthetic reaction principle of modified starch is:

[0028] Under high temperature and strong alkaline environment, sodium tripolyphosphate undergoes hydrolysis reaction in water to generate disodium hydrogen phosphate and sodium pyrophosphate. At the same time, the hydroxyl groups on the starch are ionized in small amounts and attack the phosphate to generate starch phosphate ester, thus modifying the sodium phosphate on the starch molecular chain to form modified starch.

[0029] Furthermore, the starch, ethanol solution, sodium hydroxide solution and sodium tripolyphosphate solution are used in a ratio of 3g:10mL:1g:2g, the ethanol solution is composed of anhydrous ethanol, purified water and diethylene glycol in a ratio of 6mL:3mL:0.5g, the mass fraction of the sodium hydroxide aqueous solution is 30-45%, the mass fraction of the sodium tripolyphosphate aqueous solution is 45-55%, the starch is one or more of potato starch, corn starch, soybean starch and buckwheat starch, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is lowered to room temperature, hydrochloric acid is added dropwise to the reactor, the pH of the system is adjusted to 7, suction filtration, the filter cake is washed 3 times with 70wt% ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and dried to constant weight to obtain modified starch.

[0030] Furthermore, the preparation method of the dispersing aid is: adding talcum powder and flake graphite into a ball mill for ball milling, passing through a 100-mesh sieve to obtain a mixed powder; and uniformly mixing the mixed powder with sodium dodecyl sulfate to obtain a dispersing aid.

[0031] Furthermore, the weight ratio of the talcum powder, flake graphite and sodium dodecyl sulfate is 1:2-3:2.

[0032] The present invention has the following beneficial effects:

[0033] 1. The environmentally friendly water glass-based binder for 3D sand core printing of the present invention uses high modulus sodium silicate as the water glass matrix, and mixes and modifies it with high modulus potassium silicate and a reinforcing modifier to prepare a composite water glass rich in sodium and potassium ions reinforced by a reinforcing agent. The composite water glass prepared by mixing and modifying high modulus sodium silicate, potassium silicate and a reinforcing modifier improves the immediate strength, long-term strength and moisture resistance of the sand mold during 3D sand core printing; the accelerator is prepared by modifying inorganic nanoparticles and then combining them with modified starch modified with sodium phosphate; and talcum powder, flake graphite and sodium dodecyl sulfate are used as raw materials. A dispersing agent is prepared, and the composite water glass is reinforced by the prepared accelerator and the dispersing agent, so as to modify the synergistic effect between the inorganic nanoparticles, the modified starch and the dispersing agent, and the interaction between them and the components in the composite water glass, so that when the binder is mixed with the 3D printing standard sand to form mixed sand, the fluidity of the mixed sand is further improved, and the strength index and the collapsibility of the 3D printing sand mold are improved. The water glass binder of the present application does not use organic resin as an auxiliary, and no harmful gas is generated to pollute the environment during the casting process. The used sand core sand can also be recycled to reduce the production cost, which is in line with the green and environmentally friendly manufacturing concept.

[0034] 2. The environmentally friendly water glass-based binder for 3D sand core printing of the present invention, during the preparation process, the high modulus silicate is reinforced and modified by a reinforcing modifier composed of hydroxymethyl cellulose, polyvinyl alcohol, xylitol, and sorbitol. Sodium and potassium ions have good solubility and ionization in water, and they can reduce the surface tension of water, making it easier for water molecules to wet sand particles. In addition, sodium and potassium ions can undergo ion exchange reactions with silanol groups on the surface of sand particles to form stable chemical bonds, thereby enhancing the bonding force between sand particles. The chemical bonds formed by sodium and potassium ions and silanol groups on the surface of sand particles may have high stability and are not easily destroyed even under high humidity conditions. In this way, the moisture resistance of the sand mold is maintained. Over time, the chemical reaction between the sodium and potassium ions and the silanol groups on the surface of the sand particles may become deeper and more stable, forming a stronger chemical bond. Strengthening modifiers such as hydroxymethyl cellulose and polyvinyl alcohol in the strengthening modifier can increase the viscosity and cohesion of the composite water glass, and can also form additional connection points between the sand particles through their unique molecular structure, further improving the fluidity and strength of the mixed sand composed of the binder and the 3D printing standard sand, and enhancing the hygroscopicity and water retention of the constituent materials in the modifier, which can further improve the composite water glass in a high humidity environment. Maintain a stable structure and strength.

[0035] 3. The environmentally friendly water glass-based binder for 3D sand core printing of the present invention, in the preparation process, uses nano silicon nitride, silicon powder, hollow glass microspheres as an inorganic mixture, performs surface modification on the inorganic nanoparticles, and coats and modifies the polysiloxane modified with oxygen-containing groups on the outside of the inorganic nanoparticles to obtain modified nanoparticles. Nano silicon nitride, silicon powder and hollow glass microspheres as inorganic nanoparticles have a large specific surface area and activity. The hydrophilic layer of polysiloxane modified with oxygen-containing functional groups is coated and modified on the outside of the nanoparticles, which helps to improve the compatibility of the inorganic nanoparticles with water glass, and the modified nanoparticles are used as a connection, so that the mixed sand is more easily wetted and dispersed by the water glass-based binder; the presence of the dispersing aid helps the inorganic fillers such as flake graphite and talcum powder to be evenly dispersed in the water glass, avoids agglomeration and agglomeration, and improves the fluidity of the mixed sand; the hydroxyl-modified polysiloxane, the sodium phosphate-modified modified starch and the flake graphite form a complex network structure in the composite water glass, which This structure can more effectively bond the sand particles together, and over time, the chemical reaction between the inorganic nanoparticles and the components in the composite water glass becomes more in-depth and stable, forming a stronger chemical bond. In addition, the modified starch modified by sodium phosphate has a certain hygroscopicity. Inorganic fillers such as flake graphite and talcum powder are not easily affected by water molecules and have a certain stability. They can absorb moisture in the environment and combine with it to form stable chemical bonds, thereby improving the strength performance of the printed sand mold. Modified starch and hydroxymethyl cellulose will undergo thermal decomposition under high temperature, and the gas inside the hollow glass microspheres will expand due to heat. Due to the internal and external pressure difference, the hollow glass microspheres may be deformed or broken, causing them to lose their original structure. Although nano silicon nitride and silicon powder have good stability at a certain high temperature, they will destroy the chemical bonds formed between the nanoparticles and the composite water glass at extreme high temperatures, resulting in a weakened adhesion of the sand core, which reduces the residual strength of the sand core and improves its collapsibility. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] This embodiment provides a method for preparing composite water glass for an environmentally friendly water glass-based binder for 3D sand core printing, comprising the following steps:

[0039] A1. Preparation of reinforcing modifier

[0040] Weigh: 100 g of hydroxymethyl cellulose, 70 g of polyvinyl alcohol, 40 g of xylitol, 20 g of sorbitol and 200 g of purified water, add into a reaction kettle, mix evenly, and obtain a reinforcing modifier.

[0041] A2. Preparation of composite water glass

[0042] Weigh: 750 g of sodium silicate solution and 250 g of potassium silicate solution, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, keep warm and stir for 30 minutes, reduce the temperature of the reactor to 55°C, add 100 g of a reinforcing modifier to the reactor, keep warm and stir for 40 minutes, and naturally cool to room temperature to obtain a composite water glass, wherein the modulus of the sodium silicate solution is 2.4, the solid content is 40%, and the modulus of the potassium silicate solution is 3.5, and the solid content is 35%.

[0043] Example 2

[0044] This embodiment provides a method for preparing composite water glass for an environmentally friendly water glass-based binder for 3D sand core printing, comprising the following steps:

[0045] A1. Preparation of reinforcing modifier

[0046] Weigh: 105 g of hydroxymethyl cellulose, 80 g of polyvinyl alcohol, 45 g of xylitol, 25 g of sorbitol and 250 g of purified water, add into a reaction kettle, mix well, and obtain a reinforcing modifier.

[0047] A2. Preparation of composite water glass

[0048] Weigh: 800 g of sodium silicate solution and 275 g of potassium silicate solution are added to a reactor and stirred. The temperature of the reactor is raised to reflux of the system, and the mixture is kept warm and stirred for 40 min. The temperature of the reactor is lowered to 60° C., 125 g of a reinforcing modifier is added to the reactor, and the mixture is kept warm and stirred for 50 min. The mixture is naturally cooled to room temperature to obtain a composite water glass, wherein the modulus of the sodium silicate solution is 2.7, and the solid content is 43%, and the modulus of the potassium silicate solution is 3.7, and the solid content is 40%.

[0049] Example 3

[0050] This embodiment provides a method for preparing composite water glass for an environmentally friendly water glass-based binder for 3D sand core printing, comprising the following steps:

[0051] A1. Preparation of reinforcing modifier

[0052] Weigh: 110 g of hydroxymethyl cellulose, 90 g of polyvinyl alcohol, 50 g of xylitol, 30 g of sorbitol and 300 g of purified water, add into a reaction kettle, mix well, and obtain a reinforcing modifier.

[0053] A2. Preparation of composite water glass

[0054] Weigh: 850 g of sodium silicate solution and 300 g of potassium silicate solution, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, keep warm and stir for 50 minutes, reduce the temperature of the reactor to 65°C, add 150 g of a reinforcing modifier to the reactor, keep warm and stir for 60 minutes, and naturally cool to room temperature to obtain a composite water glass, wherein the modulus of the sodium silicate solution is 3.1, and the solid content is 45%, and the modulus of the potassium silicate solution is 4.0, and the solid content is 45%.

[0055] Example 4

[0056] This embodiment provides a method for preparing a composite accelerator for an environmentally friendly water glass-based binder for 3D sand core printing, comprising the following steps:

[0057] B1. Preparation of modified nanoparticles

[0058] Nano silicon nitride, silicon powder and hollow glass microspheres are mixed uniformly in a weight ratio of 2:1:3 to obtain an inorganic mixture;

[0059] Weigh: 50 g of inorganic mixture, 20 g of ethyl 2-(triethoxysilyl)acetate, and 500 mL of anhydrous ethanol, add into a reactor and stir, raise the temperature of the reactor to 50°C, add 150 mL of 75 wt% sulfuric acid into the reactor, keep warm for 2 h, raise the temperature of the reactor to reflux, and keep warm for 8 h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at 65°C, and dry to constant weight to obtain modified nanoparticles.

[0060] B2. Preparation of modified starch

[0061] Mix anhydrous ethanol, purified water and diethylene glycol in a ratio of 6 mL:3 mL:0.5 g to obtain an ethanol solution for later use;

[0062] Weigh: 30g of potato starch, 100mL of ethanol solution, and 10g of 30wt% sodium hydroxide aqueous solution, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, add 20g of 45wt% sodium tripolyphosphate aqueous solution into the reactor, react for 4h, after the reaction is completed, lower the temperature of the reactor to room temperature, add hydrochloric acid dropwise into the reactor, adjust the pH of the system to 7, filter, wash the filter cake with 70wt% ethanol 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, and dry to constant weight to obtain modified starch.

[0063] B3. Preparation of accelerator

[0064] The modified nanoparticles and modified starch are uniformly mixed in a weight ratio of 3:1 to obtain an accelerator.

[0065] B4. Preparation of dispersing aid

[0066] Weigh: 20 g of talcum powder and 40 g of flake graphite, add them into a ball mill, and grind them. Pass them through a 100-mesh sieve to obtain a mixed powder. Mix the mixed powder with 40 g of sodium dodecyl sulfate to obtain a dispersing aid.

[0067] B5. Preparation of composite accelerator

[0068] Weigh by weight: 25 parts of accelerator and 4 parts of dispersing aid, mix evenly to obtain a composite accelerator.

[0069] Example 5

[0070] This embodiment provides a method for preparing a composite accelerator for an environmentally friendly water glass-based binder for 3D sand core printing, comprising the following steps:

[0071] B1. Preparation of modified nanoparticles

[0072] Nano silicon nitride, silicon powder and hollow glass microspheres are mixed uniformly in a weight ratio of 2.5:1.5:4 to obtain an inorganic mixture;

[0073] Weigh: 50 g of inorganic mixture, 25 g of ethyl 2-(triethoxysilyl)acetate, and 500 mL of anhydrous ethanol, add into a reactor and stir, raise the temperature of the reactor to 55°C, add 150 mL of 80 wt% sulfuric acid into the reactor, keep warm for 2.5 h, raise the temperature of the reactor to reflux the system, keep warm for 10 h, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 70°C, dry to constant weight, and obtain modified nanoparticles.

[0074] B2. Preparation of modified starch

[0075] Mix anhydrous ethanol, purified water and diethylene glycol in a ratio of 6 mL:3 mL:0.5 g to obtain an ethanol solution for later use;

[0076] Weigh: 30g corn starch, 100mL ethanol solution, and 10g 38wt% sodium hydroxide aqueous solution, add them into a reactor and stir, raise the temperature of the reactor to reflux the system, add 20g 50wt% sodium tripolyphosphate aqueous solution into the reactor, react for 5h, after the reaction is completed, lower the temperature of the reactor to room temperature, add hydrochloric acid dropwise into the reactor, adjust the pH of the system to 7, filter, wash the filter cake with 70wt% ethanol 3 times and then drain, transfer the filter cake to a drying oven at a temperature of 70°C, and dry to constant weight to obtain modified starch.

[0077] B3. Preparation of accelerator

[0078] The modified nanoparticles and modified starch are uniformly mixed in a weight ratio of 3:1.5 to obtain an accelerator.

[0079] B4. Preparation of dispersing aid

[0080] Weigh: 20 g of talcum powder and 50 g of flake graphite, add them into a ball mill, and grind them. Pass them through a 100-mesh sieve to obtain a mixed powder. Mix the mixed powder with 40 g of sodium dodecyl sulfate to obtain a dispersing aid.

[0081] B5. Preparation of composite accelerator

[0082] Weigh by weight: 30 parts of accelerator and 5 parts of dispersing aid, mix evenly to obtain a composite accelerator.

[0083] Example 6

[0084] This embodiment provides a method for preparing a composite accelerator for an environmentally friendly water glass-based binder for 3D sand core printing, comprising the following steps:

[0085] B1. Preparation of modified nanoparticles

[0086] Nano silicon nitride, silicon powder and hollow glass microspheres are mixed uniformly in a weight ratio of 3:2:5 to obtain an inorganic mixture;

[0087] Weigh: 50 g of inorganic mixture, 30 g of ethyl 2-(triethoxysilyl)acetate, and 500 mL of anhydrous ethanol, add into a reactor and stir, raise the temperature of the reactor to 60°C, add 150 mL of 85 wt% sulfuric acid into the reactor, keep warm for 3 hours, raise the temperature of the reactor to reflux, and keep warm for 12 hours. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral, and then drain, transfer the filter cake to a drying oven at a temperature of 75°C, and dry to constant weight to obtain modified nanoparticles.

[0088] B2. Preparation of modified starch

[0089] Mix anhydrous ethanol, purified water and diethylene glycol in a ratio of 6 mL:3 mL:0.5 g to obtain an ethanol solution for later use;

[0090] Weigh: 30 g of buckwheat starch, 100 mL of ethanol solution, and 10 g of 45 wt% sodium hydroxide aqueous solution, add them to a reactor and stir, raise the temperature of the reactor to reflux the system, add 20 g of 55 wt% sodium tripolyphosphate aqueous solution to the reactor, and react for 6 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, hydrochloric acid is added dropwise to the reactor, the pH of the system is adjusted to 7, and the filter cake is washed 3 times with 70 wt% ethanol and then dried, and the filter cake is transferred to a drying oven at a temperature of 75°C and dried to constant weight to obtain modified starch.

[0091] B3. Preparation of accelerator

[0092] The modified nanoparticles and modified starch are uniformly mixed in a weight ratio of 3:2 to obtain an accelerator.

[0093] B4. Preparation of dispersing aid

[0094] Weigh: 20 g of talcum powder and 60 g of flake graphite, add them into a ball mill, and grind them. Pass them through a 100-mesh sieve to obtain a mixed powder. Mix the mixed powder with 40 g of sodium dodecyl sulfate to obtain a dispersing aid.

[0095] B5. Preparation of composite accelerator

[0096] Weigh by weight: 35 parts of accelerator and 6 parts of dispersing aid, mix evenly to obtain a composite accelerator.

[0097] Example 7

[0098] This embodiment provides an environmentally friendly water glass-based binder for 3D sand core printing, including the following components in parts by weight: 80 parts of the composite water glass prepared in Example 1 and 25 parts of the composite accelerator prepared in Example 4.

[0099] Example 8

[0100] This embodiment provides an environmentally friendly water glass-based binder for 3D sand core printing, including the following components in parts by weight: 90 parts of the composite water glass prepared in Example 2 and 27 parts of the composite accelerator prepared in Example 5.

[0101] Example 9

[0102] This embodiment provides an environmentally friendly water glass-based binder for 3D sand core printing, including the following components in parts by weight: 100 parts of the composite water glass prepared in Example 3 and 30 parts of the composite accelerator prepared in Example 6.

[0103] Example 10

[0104] This embodiment provides a sand core 3D printing method, comprising the following steps:

[0105] C1. Weigh by weight: 2 parts of the environmentally friendly water glass-based binder prepared in Example 7 and 100 parts of 100-140 mesh 3D printing standard sand for later use;

[0106] C2. Evenly mix the composite accelerator in the environmentally friendly water glass-based binder with 100-140 mesh 3D printing standard sand to obtain mixed sand;

[0107] C3. Add the mixed sand and water glass into the sand mold 3D printing equipment respectively, print at a layer thickness of 0.3mm, and then print at a rate of 1g / m 2 The composite water glass is evenly sprayed on the top of the printed layer with a spraying amount of , and the printing is cyclically performed to prepare the sand core sample.

[0108] Comparative Example 1

[0109] The difference between this comparative example and Example 9 is that, in the preparation process of the composite water glass prepared in Example 3, step A1 is omitted, and no reinforcing modifier is added in step A2.

[0110] Comparative Example 2

[0111] The difference between this comparative example and Example 9 is that, in the preparation process of the composite accelerator prepared in Example 6, the modified nanoparticles in step B3 are replaced by an equal amount of the inorganic mixture in step B1.

[0112] Comparative Example 3

[0113] The difference between this comparative example and Example 9 is that, in the preparation process of the composite accelerator prepared in Example 6, step B2 is omitted, and modified starch is not added in step B3.

[0114] Comparative Example 4

[0115] The difference between this comparative example and Example 9 is that, in the preparation process of the composite accelerator prepared in Example 6, step B4 is omitted, and the accelerator prepared in step B3 is used to replace the composite accelerator.

[0116] Performance Test:

[0117] The environmentally friendly water glass-based binders prepared in Examples 7-9 and Comparative Examples 1-4 were 3D printed with reference to Example 10 to prepare sand core samples, and the fluidity of the mixed sand and the instant strength, 24h strength, 98% RH wet strength, and 800°C residual strength of the sand core samples were tested. The fluidity index of the sample was determined with reference to the standard GB / T31057.3-2018 "Testing of physical properties of granular materials Part 3: Measurement of fluidity index", the instant strength of the sample was the strength of the sample when it was 3D printed, the 24h strength was the strength of the sample after 3D printing for 24 hours, the 98% RH wet strength was the strength of the sample after 3D printing and curing in an environment with a humidity of 98% for 24 hours, and the 800°C residual strength was the strength of the sample after 3D printing and curing after being placed in an environment with a humidity of 98% for 24 hours, and the 800°C residual strength was the strength of the sample after 3D printing and molding by 800°C molten metal solution casting. The relevant strength properties were tested with reference to the standard GB / T2684-2009 "Testing methods for foundry sand and mixtures", and the specific test results are shown in Table 1:

[0118] Table 1. Performance test data of samples

[0119]

[0120]

[0121] Data Analysis:

[0122] A comparative analysis of the data in Table 1 shows that the binder prepared by the present invention is evenly mixed with 100-140 mesh 3D printing standard sand at a weight ratio of 2:100, and the fluidity index Fw of the mixed sand reaches 87. The instant strength of the sample prepared by 3D printing of the mixed sand reaches 2.63MPa, the 24h strength is 3.53MPa, the 98%RH moisture resistance reaches 2.72MPa, and the residual strength at 800°C reaches 0.53MPa. It can be seen that the binder prepared by the present invention can effectively improve the fluidity of the 3D printed mixed sand, the 3D printed sand core can be formed in real time, and the formed sample has good strength and moisture resistance. After being poured with high-temperature molten metal, the sand core has good disintegration, and no toxic gas is generated during the pouring process. The used sand core molding sand can also be recycled to reduce production costs, which is in line with the green and environmentally friendly manufacturing concept.

[0123] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0124] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0125] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. Environmentally friendly water glass-based binder for 3D sand core printing, characterized in that: The invention comprises the following components by weight: 80-100 parts of composite water glass and 25-30 parts of composite accelerator; The composite accelerator is composed of an accelerator and a dispersing aid in a weight ratio of 25-35:4-6; The accelerator is composed of modified nanoparticles and modified starch in a weight ratio of 3:1-2; The composite water glass is processed by the following steps: A1, adding hydroxymethyl cellulose, polyvinyl alcohol, xylitol, sorbitol and purified water into a reaction kettle, mixing evenly, and obtaining a reinforcing modifier; A2. Add sodium silicate solution and potassium silicate solution into a reactor and stir. Raise the temperature of the reactor to reflux the system, keep warm and stir for 30-50 minutes, lower the temperature of the reactor to 55-65°C, add a reinforcing modifier into the reactor, keep warm and stir for 40-60 minutes, and naturally cool to room temperature to obtain composite water glass.

2. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 1, characterized in that: In step A1, the weight ratio of hydroxymethyl cellulose, polyvinyl alcohol, xylitol, sorbitol and purified water is 10-11:7-9:4-5:2-3:20-30; in step A2, the modulus of the sodium silicate solution is 2.4-3.1, the solid content is 40-45%, the modulus of the potassium silicate solution is 3.5-4.0, the solid content is 35-45%, and the weight ratio of the sodium silicate solution, potassium silicate solution and reinforcing modifier is 75-85:25-30:10-15.

3. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 1, characterized in that: The modified nanoparticles are obtained by processing the following steps: B1, mixing nano silicon nitride, silicon powder and hollow glass microspheres uniformly to obtain an inorganic mixture; B2. Add the inorganic mixture, ethyl 2-(triethoxysilyl)acetate and anhydrous ethanol into a reactor and stir. Increase the temperature of the reactor to 50-60°C, add concentrated sulfuric acid into the reactor, keep the temperature for 2-3 hours, increase the temperature of the reactor to reflux the system, keep the temperature for 8-12 hours, and perform post-treatment to obtain modified nanoparticles.

4. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 3, characterized in that: In step B1, the weight ratio of the nano silicon nitride, silicon powder and hollow glass microspheres is 2-3:1-2:3-5; in step B2, the amount ratio of the inorganic mixture, ethyl 2-(triethoxysilyl)acetate, anhydrous ethanol and concentrated sulfuric acid is 5g:2-3g:50mL:15mL, and the mass fraction of the concentrated sulfuric acid is 75-85%. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter is filtered, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 65-75°C and dried to constant weight to obtain modified nanoparticles.

5. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 1, characterized in that: The preparation method of the modified starch comprises: adding starch, ethanol solution and sodium hydroxide aqueous solution into a reactor and stirring, raising the temperature of the reactor to reflux the system, adding sodium tripolyphosphate aqueous solution into the reactor, reacting for 4-6 hours, and post-treating to obtain the modified starch.

6. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 5, characterized in that: The starch, ethanol solution, sodium hydroxide solution and sodium tripolyphosphate solution are used in a ratio of 3g:10mL:1g:2g, the ethanol solution is composed of anhydrous ethanol, purified water and diethylene glycol in a ratio of 6mL:3mL:0.5g, the mass fraction of the sodium hydroxide aqueous solution is 30-45%, the mass fraction of the sodium tripolyphosphate aqueous solution is 45-55%, the starch is one or more of potato starch, corn starch, soybean starch and buckwheat starch, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is lowered to room temperature, hydrochloric acid is added dropwise to the reactor, the pH value of the system is adjusted to 7, suction filtration is performed, the filter cake is washed 3 times with 70wt% ethanol and then dried, the filter cake is transferred to a drying oven at a temperature of 65-75°C, and dried to constant weight to obtain modified starch.

7. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 1, characterized in that: The preparation method of the dispersing aid comprises: adding talcum powder and flake graphite into a ball mill for ball milling, and passing through a 100-mesh sieve to obtain a mixed powder; and uniformly mixing the mixed powder with sodium dodecyl sulfate to obtain the dispersing aid.

8. The method for preparing an environmentally friendly water glass-based binder for 3D sand core printing according to claim 7, characterized in that: The weight ratio of the talcum powder, flake graphite and sodium dodecyl sulfate is 1:2-3:2.

Citation Information

Patent Citations

  • Inorganic binder for 3D printing and preparation method thereof

    CN114230211A